2005
DOI: 10.3748/wjg.v11.i46.7308
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate reduces ischemia-reperfusion injury of the small intestine

Abstract: AIM:To evaluate whether pyrrolidine dithiocarbamate (PDTC), an enhancer of HO production, attenuates intestinal IR injury.METHODS: E i g h t e e n m a l e ra t s w e r e ra n d o m l y allocated into three groups: (a) sham; (b) IR, consisting of 30 min of intestinal ischemia, followed by 2-h period of reperfusion; and (c) PDTC treatment before IR. Intestinal microvascular perfusion (IMP) was monitored continuously by laser Doppler flowmetry. At the end of the reperfusion, serum samples for lactate dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Support for this theory is provided by the observation that ischemic injury to the small bowel is most severe at the tip and is attenuated by intraluminal perfusion with oxygenated saline 26 . A variety of associations between ascorbic acid and IR injury has been described recently [27][28][29][30][31] . Cizova et al 27 demonstrated that the ascorbic and uric acid concentrations increased generally after IR in comparison to intact controls, but this increase was not sufficient to prevent lipid peroxidation in serum and intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this theory is provided by the observation that ischemic injury to the small bowel is most severe at the tip and is attenuated by intraluminal perfusion with oxygenated saline 26 . A variety of associations between ascorbic acid and IR injury has been described recently [27][28][29][30][31] . Cizova et al 27 demonstrated that the ascorbic and uric acid concentrations increased generally after IR in comparison to intact controls, but this increase was not sufficient to prevent lipid peroxidation in serum and intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The development of injuries in early reperfusion was studied using 60-min ischemia and 120-min reperfusion periods. These terms are not lethal to animals but cause damage to the organ [Mallick et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB p65 protein has been reported to exhibit increased expression in nuclear extracts from local mucosal tissue specimens of patients with inflammatory bowel disease [10,11] . Recently reports have been published to evaluate the inflammation suppressing effect of antisense oligonucleotide for NF-κB (p65) administered to mice with TNBS-induced enteritis (a model of Crohn's disease) [12] and mice with DSS-induced colitis (a model of ulcerative colitis) [13] or ischemia-reperfusion injury of the small intestine [14] . It has been reported that NF-κB binds to the DNA sequence termed "κB sequence" and induces expression of the genes regulated by this sequence.…”
Section: Discussionmentioning
confidence: 99%